2014
DOI: 10.1103/physrevb.89.144422
|View full text |Cite
|
Sign up to set email alerts
|

Spin-cycloid instability as the origin of weak ferromagnetism in the disordered perovskiteBi0.8La0.2Fe0.5Mn0.5O

Abstract: Powder neutron diffraction and magnetometry studies have been conducted to investigate the crystallographic and magnetic structure of Bi0.8La0.2Fe0.5Mn0. 5O3. The compound stabilizes in the Imma orthorhombic crystal symmetry in the measured temperature range of 5 to 380 K, with a transition to antiferromagnetic order at TN≈240 K. The spin cycloid present for BiFeO3 is found to be absent with 50% Mn3+ cation substitution, leading to G-type antiferromagnetic order with an enhanced out-of-plane canted ferromagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…40 In a broad context, the origin of enhancement in the magnetic properties of BFO could be either due to the formation of AFM/FM core/shell-like structures or the suppression of its cycloidal spin structure, which essentially leads to a net magnetization due to the manifestation of 'canted' spins. 41 Therefore, temperature dependent magnetization studies were carried out to investigate the possible origin of the observed magnetism in these BDFO x nanostructures. gradual increment and a drastic decrement of ZFC magnetic moments (M ZFC ) with decreasing temperature from 300 K to 5 K.…”
Section: Magnetization Studiesmentioning
confidence: 99%
“…40 In a broad context, the origin of enhancement in the magnetic properties of BFO could be either due to the formation of AFM/FM core/shell-like structures or the suppression of its cycloidal spin structure, which essentially leads to a net magnetization due to the manifestation of 'canted' spins. 41 Therefore, temperature dependent magnetization studies were carried out to investigate the possible origin of the observed magnetism in these BDFO x nanostructures. gradual increment and a drastic decrement of ZFC magnetic moments (M ZFC ) with decreasing temperature from 300 K to 5 K.…”
Section: Magnetization Studiesmentioning
confidence: 99%
“…On the other hand, past Monte Carlo classical spin simulations have explored the effect of large scale random chemical disorder indicating a high population of anti-site defects in a ferrimagnet ultimately prohibiting long-range ferrimagnetism, and giving almost zero global magnetization, except for small local spin-canting effects. 40 From these results, it seems reasonable that the difficulty in synthesizing O-phase in the bulk is related to the low energy associated with (partially) disordered BFCO structures. Evidently, obtaining chemical ordering in bulk samples of BFCO is experimentally difficult.…”
Section: Rationalizing the Resultsmentioning
confidence: 89%
“…Monte Carlo simulations were performed for a 10 monolayer FM/AF bilayer with a polycrystalline microstructure, using the custom-written FullMonty software. 39) Single SF dynamics using a Glauber heat-bath were used to model the thermal evolution of the structure. 40) The model used is an adaptation of the model originally presented in Ref.…”
Section: Theoreticalmentioning
confidence: 99%